Identifying and Developing Realistic VR Fire Drill Elements based on User-Centered Design - 전승곤 (The Graduate School, Ajou University, 2020)
Although virtual reality (VR) programs to provide firefighting training continue to be developed and adopted, our investigation with 15 firefighters indicates that a current VR training system tends to convey behavioral tips and does not sufficiently reflect actual firefighters' needs and realities in the field. It often provides somewhat simplified fire simulations and actually lowers the effectiveness of the training. In this paper, we employ Human-Computer Interaction (HCI) methods to examine and identify core elements in firefighting scenarios and develop a VR system that incorporates such elements. We evaluate our system with respect to presence and three design components of the VR simulation (i.e., reality, meaning, play) through two user studies. The first user study results demonstrate greater user experience and perception toward the four elements in firefighting training with our VR system compared to the existing one. Then, we have collected feedback of the study participants, modified the VR training program and evaluated it again with 18 new participants. The results of the second study shows that the continuous application of the HCI method makes the system to provide high user experience. We discuss design implications (e.g., move control, degree of freedom, sight hindrance by smoke, unexpected events) of our study that are expected to help implement and provide an effective VR training system for firefighters.
학위논문(석사)--아주대학교 일반대학원 :컴퓨터공학과,2020. 8
Keywords: Firefighting training system; Presence; User study; User-centered design; Virtual reality